1993
DOI: 10.1111/j.1439-0442.1993.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Intratracheal Pressure in the Horse under Field Conditions as a Method for Evaluation of Upper Airway Resistance

Abstract: Summary Recording of intratracheal pressure during exercise as a method for evaluating upper airway obstruction in the horse has previously been carried out on the treadmill. In the present study the method was applied to normal horses, outdoors under field conditions, to assess its usefulness for analysis of respiratory problems mainly occurring under racing conditions. The horses examined performed a standardized exercise test during which the intratracheal pressure was recorded with a tape recorder receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Several measurement techniques and definitions for upper airway pressure have been used. A catheter (polyethylene, polytetrafluoroethylene, teflon tubing) is placed percutaneously through the wall of the trachea into the cranial part of the trachea (Derksen et al, 1986;Shappell et al, 1988;Funkquist et al, 1988;Williams et al, 1990a;Lumsden et al, 1993;Roethlisberger-Holm, 1993) or nasotracheally (Williams et al, 1990a;Williams et al, 1990b;Ducharme et al, 1994;Rehder et al, 7995)into the pharynx and the cranial part of the trachea. Williams and assistants (f990a) have shown that the pressure recordings via a transnasal catheter are not different from recordings made by a transtracheal catheter but less invasive and therefore more suitable for clinical use.…”
Section: Techniquesmentioning
confidence: 99%
“…Several measurement techniques and definitions for upper airway pressure have been used. A catheter (polyethylene, polytetrafluoroethylene, teflon tubing) is placed percutaneously through the wall of the trachea into the cranial part of the trachea (Derksen et al, 1986;Shappell et al, 1988;Funkquist et al, 1988;Williams et al, 1990a;Lumsden et al, 1993;Roethlisberger-Holm, 1993) or nasotracheally (Williams et al, 1990a;Williams et al, 1990b;Ducharme et al, 1994;Rehder et al, 7995)into the pharynx and the cranial part of the trachea. Williams and assistants (f990a) have shown that the pressure recordings via a transnasal catheter are not different from recordings made by a transtracheal catheter but less invasive and therefore more suitable for clinical use.…”
Section: Techniquesmentioning
confidence: 99%